Compact triple-passband bandpass filter based on new modified stepped impedance resonators. Issue 6 (June 2015) - Wu, Hung-Wei; Lin, Chien-Chih; Chen, Yu-Fu; Lee, Hsin-Ying
Abstract This study proposed a triple-passband bandpass filter with compact size, low loss and high passband selectivity. The filter includes two coupled stepped impedance resonators (SIRs) and two embedded stub-loaded stepped impedance resonators (SL-SIRs), connected with coupling scheme at the symmetric plane of the filter. The filter is designed to have triple-passband at 2.4, 3.5 and 5.2 GHz for worldwide interoperability for microwave access (WiMAX) applications. By properly tuning the impedance ratio and physical length ratio of the SL-SIRs, the three passbands can be easily determined, at the same time, achieving the high passband selectivity and wide stopband. Besides, the transmission zeros near passband edges of each passband are generated by the proposed filter with cross-coupling structure. The measured results are in good agreement with the full-wave electromagnetic (EM) simulation results.